FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TERHADAP PENDAPATAN PEMBUDIDAYA IKAN NILA (STUDI KASUS: KOTA TASIKMALAYA) - Fikri Nashrullah; Atikah Nurhayati; Subiyanto Subiyanto; Asep Agus Handaka Suryana (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2021)
This study aims to identify various factors that affect the productivity of tilapia aquaculture in Tasikmalaya City. The location of this study was eight sub-districts of Tasikmalaya City. This research was conducted from February 2021 to November 2021. This is a quantitative and confirmatory descriptive study. The required quantitative data are primary and secondary data. The primary data were collected through two types of collection techniques, namely observation and interviews, followed by filling out questionnaires by the respondent. Meanwhile, the secondary data in this study was obtained by downloading data from the websites of the relevant agencies and the district statistical center, as well as from previous studies. In addition to several characteristics of cultivators and cultivation businesses, several conditions and obstacles experienced by cultivators are used as complementary research data. The respondents of this study are tilapia cultivators in Tasikmalaya City. The choosing of respondents was conducted by accidental sampling method. The results showed that the factors that significantly affected the productivity of tilapia aquaculture in Tasikmalaya City consisted of land size, feed price, quantity of feed, and price of fingerlings.